Advances in Our Understanding of “Resistance” to Antiplatelet Agents for Prevention of Ischemic Stroke - Philip B. Gorelick; Muhammad U. Farooq (Stroke Research and Treatment)
We review the role of aspirin and clopidogrel for prevention of ischemic stroke and explore the concept of antiplatelet therapy resistance both from a laboratory and clinical perspective and genetic polymorphisms that might influence platelet reactivity with clopidogrel administration. Debates have raged over the years about the application of platelet function tests in clinical practice. We conclude that platelet function testing is not indicated in routine clinical practice. This recommendation is supported by clinical guideline statements, a lack of a global platelet function measure, and limitations of current platelet function test methods as applied in practice. We discuss a recently hypothesized hierarchy of patient characteristics in relation to which patients are most likely to benefit from platelet function studies based on acuity (i.e., risk) of cardiovascular disease. A focus of antiplatelet therapy administration should include emphasis on compliance/adherence and in the example of aspirin, use of well-absorbed forms of aspirin and avoidance of drugs that may interact with aspirin to inhibit its mechanism of action (e.g., certain nonsteroidal anti-inflammatory drugs).